2022
DOI: 10.1021/acsearthspacechem.1c00433
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons (PAHs) in Interstellar Ices: A Computational Study into How the Ice Matrix Influences the Ionic State of PAH Photoproducts

Abstract: It has been experimentally observed that water–ice-embedded polycyclic aromatic hydrocarbons (PAHs) form radical cations when exposed to vacuum UV irradiation, whereas ammonia-embedded PAHs lead to the formation of radical anions. In this study, we explain this phenomenon by investigating the fundamental electronic differences between water and ammonia, the implications of these differences on the PAH–water and PAH–ammonia interaction, and the possible ionization pathways in these complexes using density funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…We have theoretically investigated complexes formed between a cyclic water trimer and a tricyclic PAH molecule (acenaphthylene) via O–H···π bonds, displaying distinct spatial configurations. These systems are similar to probable candidates to be found in cold extraterrestrial environments . However, there exist intrinsic difficulties in determining infrared emission bands of pure PAHs .…”
Section: Conlusionssupporting
confidence: 61%
See 1 more Smart Citation
“…We have theoretically investigated complexes formed between a cyclic water trimer and a tricyclic PAH molecule (acenaphthylene) via O–H···π bonds, displaying distinct spatial configurations. These systems are similar to probable candidates to be found in cold extraterrestrial environments . However, there exist intrinsic difficulties in determining infrared emission bands of pure PAHs .…”
Section: Conlusionssupporting
confidence: 61%
“…These systems are similar to probable candidates to be found in cold extraterrestrial environments. 65 However, there exist intrinsic difficulties in determining infrared emission bands of pure PAHs. 66 Then, we have focused on the ddu ↔ ddd flipping process of the trimer anchored on the aromatic plane, which may favor a stable and highly dipolar structure of the resulting complex at interstellar temperatures.…”
Section: ■ Conlusionsmentioning
confidence: 99%
“…Considering now diffuse clouds with highradiation field to support our prereactive models for photodissociation of these complexes, it is necessary to take a closer look at the electronic structure between their moieties. A recent study 25 has reported an MO mixing analysis that allows rationalizing the experimental observation of PAHs trapped in ice matrices. In general, PAHs become cationic when exposed to UV radiation because of the smaller superposition involving the lone pair HOMO of the water molecules with π-filled MOs of a PAH.…”
Section: Kohn−sham Mo Mixing Between the Pahs And Water Dimermentioning
confidence: 99%
“…Regarding the physicochemical processes in the ISM, the predissociative stage may be modeled by a microhydrated PAH molecule, and a related phenomenon consists of photoionization of the PAH in the presence of the Lyman-α field. As noticed for the ionic forms at temperatures above 120 K, it is expected that the OH – ion reacts with the PAH + , and H + diffuses through solvation shells, mainly when exposed to VUV irradiation. , Theoretical investigations on the reactivity of these processes are scarce in the literature. Recently, ten Brinck et al have employed time-dependent density functional theory (TD-DFT) calculations to rationalize the reactivity of ice-embedded PAHs. Their results are in line with the experimental observation that, in the presence of water, PAHs become cationic when exposed to VUV irradiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation